Dendrimer-modified magnetic nanoparticles as a sorbent in dispersive micro-solid phase extraction for preconcentration of metribuzin in a water sample. Issue 44 (26th October 2020) - Moghadam, Mojtaba Rahimi; Zargar, Behrooz; Rastegarzadeh, Saadat
Abstract : This study was conducted to synthesize magnetic nanoparticles modified with generation 5 polyamidoamine dendrimer and apply them as a sorbent in the dispersive-micro-solid phase extraction method for preconcentration of metribuzin in water samples. Abstract : This study was conducted to synthesize magnetic nanoparticles (MNPs) modified with generation 5 (G5 ) polyamidoamine (PAMAM) dendrimer and apply them as a sorbent in the dispersive-micro-solid phase extraction (D-μ-SPE) method for preconcentration of metribuzin in water samples. The characterization of synthesized nanoparticles was performed by Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), scanning electron microscopy (SEM), dynamic light scattering (DLS), and vibrating sample magnetometry (VSM). The effects of sample solution pH, the terminal group type, dendrimer generation, ionic strength, sorbent dosage, and desorption conditions on the removal efficiency were investigated. The linear range was calculated from 25–1000 μg L −1 and the LOD was 10 μg L −1 . The recovery percentages for the spiked real samples ranged from 95.3% to 103.5% and relative standard deviations (RSD%) were in the range of 87.2–92.1 and 4.2 to 6.3 ( n = 5) respectively. Applying the method developed in this work in water samples revealed good extraction recoveries with a RSD of 5.6–7.3%.